KAJIAN LABORATORIUM PENGGUNAAN ASPAL MODIFIKASI POLIMER DAN PENGARUH SUHU PEMADATAN TERHADAP KARAKTERISTIK MARSHALL DAN DURABILITAS PADA CAMPURAN HRS-BC - , Setyaningsih, Prof. Ir. Suryo Hapsoro Tri Utomo, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Performance of highway flexible pavement layers can be improved by increasing the quality of binding material. One of technology in improving the quality of asphalt is to add synthetic elastomer polymer material. Interlocking between asphalt and aggregate in hot mix asphalt are influenced by mixing temperatures and compaction temperatures. The purpose of the study is: (1) to determine the differences in Marshall characteristics and HRS-BC mixture durability which is using asphalt pen 60/70 as a polymer modified asphalt , (2) to determine the effect of variations in compaction temperature and immersion time toward the value of Marshall characteristics and mixture durability of HRS-BC modified asphalt. This study conducted variation of the immersion time, which are 0.5, 24, 72 and 120 hours, to determine the differences in Marshall characteristics and mixture durability. The differences of Marshall characteristic can be obtained from Marshall test at 0.5 h of immersion. While the differences of durability can be obtained from Marshall test at 0.5, 24, 72 and 120 hours of immersion. The compaction temperature variation of 165oC, 155oC and 145oC with the immersion time of 0.5, 24, 72, and 120 hours are conducted on polymer modified asphalt mixtures to determine the effect of compaction temperature towards the Marshall characteristics and durability. Based on the analysis result, polymer modified asphalt mixture has Marshall characteristic (VMA, VFWA, VITM, stability, flow and Marshall Quontient) and durability (index of residual strength, the first durability index and second durability index) mixture that higher than asphalt pen 60 / 70. The decreasing of compaction temperature in polymer modified asphalt tends to decrease the value of VMA, VITM, stability, flow, Marshall Quotient and residual strength index, but it increase the value VFWA, the first durability index, and the second durability index.